Position and Authority of the Constitutional Court as a Guardian of the Constitution - Arifin, Firdaus (Dinasti Research, 2024)
The provisions of Article 24C of the 1945 Constitution have given the Constitutional Court the authority of the Constitutional Court as an institution that resolves cases related to the Indonesian constitution, which makes the Constitutional Court a guardian of the constitution. A special feature of the Constitutional Court is the authority to conduct judicial review. The role of the Constitutional Court as a guardian of the constitution is seen as incomplete because there is no regulation of constitutional questions. This research is a normative juridical research with a statutory approach and a conceptual approach, secondary data is obtained through a library study and then analyzed qualitatively juridically. The results of the study state that the Constitutional Court as the guardian of the constitution is positioned as a constitutional state organ with the philosophical basis of the authority of the Constitutional Court based on substantive justice. The realization of the Constitutional Court as a guardian of the constitution will be sharper if there is a constitutional question mechanism. Therefore, it is necessary to change the legal basis related to the authority of the Constitutional Court which includes the constitutional question as the authority of the Constitutional Court.